Mechanical and Mesoscale Analyses of Cement Stabilized Macadam Prepared by Vibratory and Nonvibratory Mixing Techniques - Jijing Wang; Zhihua Tan (Advances in Civil Engineering)
The objective of this study is to analyze the effects of mixing techniques on the mechanical behavior and meso-structure of cement-treated aggregate. Different specimens were prepared by vibratory and nonvibratory mixing techniques. X-ray CT scans were performed to illustrate the distribution of cement mortar on aggregate. The strength, modulus, and fatigue tests under different stress states were tested to reveal the impacts of mixing techniques. Then, the relationships between strengths and loading rates and that between moduli and stress levels were established. Hereafter, the S-N fatigue equation that modified with stress ratio related to loading rates was used to describe the fatigue performance. The results indicate that the cement mortar of specimens prepared by vibratory mixing was well-distributed on aggregates. The strength, modulus, and fatigue life of the specimens prepared by vibratory mixing were higher under the test condition threshold. Moreover, the growth rate of strength and modulus with loading for specimens prepared by vibratory mixing was slightly larger than that for specimens prepared by nonvibratory mixing. Compared with the cement-treated aggregates specimens prepared by nonvibratory mixing, the fatigue life of cement-treated aggregates specimens prepared by vibratory mixing had more stable stress sensitivity.